Glass - Cackett, Susan; Nevett, Louise (New York : Gloucester Press, 1988)
Examines what glass is made from, various glass products, the design and production, special glass, and recycling.
Includes index.
Booklist.
6.4
3-6
Keywords: Glass -- Juvenile literature; Glass; Glass; Glass